(untitled) (International Journal of Engineering and Computer Science, 2021)
The emergence of advanced AI technologies such as expert systems, fuzzy logic, neural networks, and genetic algorithms can directly address people’s health needs by providing personalized advice to users while at the same time collecting valuable data related to aspects of diseases and treatments. These technologies have been in use for quite some time and have evolved to the point where they have matured into practical decision support systems that can be used to assist people in health management and promotion efforts. This chapter presents a survey of the current progress and ongoing research in the area of health-related AI technology and end-user products. With the ever-growing trajectory of technology and the increasing demand to reduce healthcare costs while providing better quality healthcare, employing AI as part of or adjunct to medical processes will become increasingly important from both economic and social perspectives. The classical problems of the healthcare industry include providing people with new and better treatments, more effective ways of preventing, detecting, and combating multifaceted chronic diseases, and ways of caring for the ever-increasing numbers of senior citizens.